1999
DOI: 10.1111/j.1365-2141.1999.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial occurrence of chronic neutrophilic leukaemia

Abstract: A father and son who both developed chronic neutrophilic leukaemia (CNL) are reported. The father, aged 63, had been exposed to radioactive fallout after the atomic bomb attack on Hiroshima; he presented with hepatosplenomegaly and neutrophilic leucocytosis, and died of intracerebral haemorrhage 1 month after diagnosis. 4 years later his son, then aged 44, presented with neutrophilic leucocytosis. Leukaemic transformation to acute myelogenous leukaemia (AML-M1) occurred, and he died of refractory leukaemia 4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…For blast phase, standard induction chemotherapy was successful at attaining a second chronic phase in one patient only [37]. In the remaining patients the leukemia was either refractory, the marrow remained hypoplastic following induction chemotherapy or death occurred during attempts at remission induction [5,32,38,41]. A similar situation has been observed among patients with refractory progressive neutrophilia [5,44,46].…”
Section: Induction Chemotherapymentioning
confidence: 65%
See 1 more Smart Citation
“…For blast phase, standard induction chemotherapy was successful at attaining a second chronic phase in one patient only [37]. In the remaining patients the leukemia was either refractory, the marrow remained hypoplastic following induction chemotherapy or death occurred during attempts at remission induction [5,32,38,41]. A similar situation has been observed among patients with refractory progressive neutrophilia [5,44,46].…”
Section: Induction Chemotherapymentioning
confidence: 65%
“…At that time, only 150 cases had been reported in the literature [29,31,32]. A critical review of the literature applying the then recently developed WHO diagnostic criteria, could only confirm this diagnosis in 40 cases, indicating the true rate of occurrence of what is now considered CNL was even lower [5,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. In this data set of WHO-defined CNL, the median age at diagnosis was 66 years (range: 15 -86) and 56% were males [5].…”
Section: Epidemiology and Demographicsmentioning
confidence: 99%
“…Some patients exhibit a prolonged stable phase with minimal or no intervention, but there is a definite risk of death from either leukemic transformation or progressive, refractory neutrophilic leukocytosis, as further demonstrated by this report. 1,8,10,12 Thus, the use of aggressive therapeutic strategies for patients who can tolerate such an approach appears warranted. A palliative approach may be reasonable in older patients with a poor performance status or significant co-morbidities, but for patients without these features alternative strategies should be considered, such as allogeneic bone marrow or peripheral stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies for the BCR/ABL rearrangement, which must be negative before this diagnosis can be made, have been performed only in cases described since 1992, accounting for fewer than 10 reported cases. [5][6][7][8][9][10][11][12] This study is the largest reported series of wellcharacterized patients with CNL and allows a more detailed description and understanding of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, platelet function was not evaluated in any of the 40 patients [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Qualitative platelet abnormalities are commonly found in patients with myeloproliferative disorders (MPDs) such as chronic myelogenous leukemia, myeloid metaplasia and myelofibrosis, polycythemia vera, and essential thrombocythemia [26,27].…”
mentioning
confidence: 99%